2018
DOI: 10.1080/14763141.2017.1409259
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy between optical and inertial motion capture systems for assessing trunk speed during preferred gait and transition periods

Abstract: Motion capture through inertial sensors is becoming popular, but its accuracy to describe kinematics during changes in walking speed is unknown. The aim of this study was to determine the accuracy of trunk speed extracted using an inertial motion system compared to a gold standard optical motion system, during steady walking and stationary periods. Eleven participants walked on pre-established paths marked on the floor. Between each lap, a 1-second stationary transition period at the initial position was inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Therefore, it is essential to assess the movement patterns of VI players in the most natural conditions possible. Inertial motion capture systems (IMC) have become highly popular in recent years, providing acceptable measurements of human kinematics in different movement conditions 13,14 . Especially for sports activities, IMCs allows recordings of kinematic data in more natural conditions, such as open spaces like football courts.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is essential to assess the movement patterns of VI players in the most natural conditions possible. Inertial motion capture systems (IMC) have become highly popular in recent years, providing acceptable measurements of human kinematics in different movement conditions 13,14 . Especially for sports activities, IMCs allows recordings of kinematic data in more natural conditions, such as open spaces like football courts.…”
Section: Introductionmentioning
confidence: 99%
“…Pearson’s correlation coefficient between the estimated level of fatigue and self-reported fatigue level was used as the evaluation criterion (as shown in Equation ( 5 )). The coefficient can be categorized as weak ( ), moderate ( ), strong ( ), or excellent ( ) [ 45 , 46 ]. For each K-fold cross-validation, the training phase was stopped when the accuracy of the validation set started to decrease, and the corresponding CNN-based regression was saved.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…An interesting job is the one developed by Fleron et al [34], where the objective was to determine the accuracy of trunk speed while walking, using an inertial motion system compared to a gold standard optical motion system. It was concluded that trunk speed extracted from inertial systems has a reasonable precision during the gait movement, but the accuracy was reduced during the transition periods.…”
Section: Motion Capture Based On Inertial-magnetic and Optical Systemsmentioning
confidence: 99%